Four Poems. (2nd January 2019) - Jialu, Mi; Klein, Lucas; Day, Michael; Turner, Matt; Weng, Haiying
Abstract : These four poems by Mi Jialu show a personal contemplation on the torturous human condition Inflicted by historical traumas, environmental crisis, and diasporic alienation. Through a gaze of a surreal lens, the poet seeks to express the inexpressible haunted by memory, dreams, and ghosts. With a more psychological quest, the poet embarks on a journey into the heart of darkness for self-redemption and spiritual illumination.